Stimulating CO2 sequestration of aluminum-rich refining slag (ARS): A proposed method of preventing katoite formation using desulfuration gypsum. (1st January 2023) - Wang, Xue; Fan, Yufeng; Ni, Wen; Fu, Pingfeng
Abstract: As CO2 mineralization is a highly promising method for carbon capture and storage (CCS 1 ) to achieve carbon neutrality, special tailings and metallurgical slags can be used as CO2 mineralization feedstocks to prepare building materials. Generated during the steel refining process, aluminum (Al)-rich refining slag (ARS) can be employed as CO2 feedstocks. Hence, this study investigated ARS′ ability in CCS by accelerated carbonation after hydration curing. Then, desulfuration gypsum (DG) was used to stimulate the aluminates in ARS. The results showed that DG significantly enhanced the mechanical properties and carbon-capturing capacity of ARS, achieving 33.93 MPa and 18.63% CO2 uptake after a three-day carbonation curing of ARS-DG samples, making it 111.23% and 99.01% higher than those of ARS samples, respectively. QXRD, SEM, TG/DTG, and FTIR were then conducted, and investigations demonstrated that katoite was formed after the hydration reactions of C12 A7 and C3 A in ARS. However, katoite's very low carbon reactivity limited the potential of CO2 sequestration for ARS. Therefore, this study also explored a new way to avoid the formation of chemically stable katoite by adding DG, which transformed hydration products from katoite to high-carbon reactive hemicarbonate. Consequently, the formed CaCO3 phase changed from two types (vaterite and aragonite) to three (calcite, vaterite, and aragonite) after DG addition. This study offers an effective approach for the CO2 mineralization of ARS to make building materials. Highlights: Aluminum-rich refining slag (ARS) has a high potential for CO2 capture. Katoite, the hydration product of ARS, is hard to carbonate. DG addition transfers the hydration product from katoite to hemicarbonate. DG greatly improves the mechanical and CO2 capture performances of ARS.